Atributos químicos do solo em áreas de produção de banana (musa spp.) - Santos, André Luís Pereira dos (2019)
The use and management of soil by different systems cause changes in the physical and chemical quality of its attributes. This study aimed to evaluate the quality of a dystrophic Red-Yellow Latosol, based on changes in chemical attributes in a sloping area of banana farming. A randomized blocks experimental design with a 3x2 factorial arrangement was used, consisting of three transects in the declining area (upper, median, and lower) and two depths (0-20 cm and 20-40 cm) in each transect for collecting soil samples, with three replications. Undeformed soil samples were randomly collected in the study area for chemical analyses. The following variables were evaluated: pH, sodium (Na+), exchangeable aluminum (Al+3), exchangeable cations (K+, Ca+2, and Mg+2), available phosphorus (P), exchangeable acidity (H++Al+3), organic matter (OM), sum of bases (SB), cation exchange capacity (CEC), and aluminum saturation (m). The higher concentration of organic matter in the experimental area surface layer contributes to increasing cation exchange capacity, retaining bases, and increasing the pH, directly reflecting in the acidity decrease. The soil deepest layer had an increase in aluminum levels, leading to an increased Al saturation, which caused a decrease in the base saturation. Regarding the relief of the experimental area, the lower and median regions had higher values of exchangeable acidity and aluminum saturation. The upper region had higher values of the sum of bases and base saturation and lower losses and a greater increase in organic matter contents due to banana leaves deposited on the soil surface, which is a common activity in the region where the experiment was installed. The use of multivariate techniques is a very useful tool in the analysis of data related to soil chemical attributes, with samples collected from different depths in sloping areas of banana farming systems.